Concentration and size of gravel in relation to neutron miosture and density probe calibration - Lal, R. (1979)
The effects of four gravel concentrations (0, 20, 40, and 60 percent by weight) and three gravel size fractions (4-8 mm, 8-15 mm, and 15-40 mm) on the calibration of a neutron moisture meter and density probe was investigated for a beach sand and a clayey tropical Alfisol (Oxic Paleustalf). The slope of the regression line of the calibration curve relating neutron count ratio with volumetric moisture content of gravel-free sand was statistically significantly different from that of three gravel-sand mixtures. The calibration curve of three gravel-sand mixtures was statistically identical. For the gravel-soil mixtures, the slope of the calibration curve generally decreased with increased gravel concentration. The statistical comparison of the regression lines for the 4-8 mm gravel size fraction indicated that the slope coefficient of the calibration curve of only 60 percent gravel-soil mixture was significantly lower than that of 0, 20, and 40 gravel percentages. For the 8-15 mm gravel size fraction, the slopes of the regression lines of 40 and 60 percent gravel-soil mixtures were similar and significantly lower than that of 0 and 20 percent gravel concentrations. Gravel size had no effect on the calibration curve in the gravel-sand mixtures. In the gravel-soil mixtures, for 20 and 40 percent gravel concentrations, 4-8 mm gravel size had a significantly higher slope coefficient of the regression equations, compared with the 8-15 mm size fraction. The slope of the regression equation relating density count ratio with dry density significantly decreased with an increase in gravel concentration for 40 and 60 percent, compared with 0 and 20 percent gravels for gravel-soil mixtures. Heterogeneity of tropical soils, with regard to variations in texture and gravel concentrations, may necessitate a detailed calibration of the neutron moisture meter prior to its use on large watersheds.